An Item Response Theory-Based Scoring of the South Oaks Gambling Screen–Revised Adolescents. (October 2022) - Anselmi, Pasquale; Colledani, Daiana; Andreotti, Alessandra; Robusto, Egidio; Fabbris, Luigi; Vian, Paolo; Genetti, Bruno; Mortali, Claudia; Minutillo, Adele; Mastrobattista, Luisa; Pacifici, Roberta
The South Oaks Gambling Screen–Revised Adolescent (SOGS-RA) is one of the most widely used screening tools for problem gambling among adolescents. In this study, item response theory was used for computing measures of problem gambling severity that took into account how much information the endorsed items provided about the presence of problem gambling. A zero-inflated mixture two-parameter logistic model was estimated on the responses of 4, 404 adolescents to the South Oaks Gambling Screen–Revised Adolescent to compute the difficulty and discrimination of each item, and the problem gambling severity level (θ score) of each respondent. Receiver operating characteristic curve analysis was used to identify the cutoff on the θ scores that best distinguished daily and nondaily gamblers. This cutoff outperformed the common cutoff defined on the sum scores in identifying daily gamblers but fell behind it in identifying nondaily gamblers. When screening adolescents to be subjected to further investigations, the cutoff on the θ scores must be preferred to that on the sum scores.